The effect of interest and attitude on public comprehension of news with data visualization - Sánchez-Holgado, Patricia; Arcila-Calderón, Carlos; Frías-Vázquez, Maximiliano (Frontiers in Communication, 2023)
In recent years, data visualization has been gaining space in journalism, not only in the specialized press, but also in the general press. The objective of this article is to analyze whether there are differences between the impact of receiving a traditional news item and that of a news item with data visualization, in terms of interest, comprehension and attitudes towards data visualization. For this, a study (N=700) was carried out with two experimental conditions (traditional news versus news with data visualization), using scientific and health communication news. Moderated mediation analysis were performed to understand how data visualization affects factors such as attitude, or interest, and affects public comprehension. The results showed significant indirect effects that indicate that reading a data visualization news item increases comprehension and, with it, positive attitudes towards data visualization. Variables related to comprehension and interest have been found to have a significant impact on attitudes towards data viewing, opening new lines of research to delve into the factors that affect data-driven news performance.